Tantangan Dan Solusi: Strategi Politik Kepala Madrasah Dalam Meningkatkan Kualitas Pendidikan - Ana, Ana Imroatul Mufidata; Munifah (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2025)
According to Maxwell, the success or failure of an organization depends on leadership, and the same applies to madrasas, which rely on the headmaster's leadership. An interesting aspect to study is how the headmaster devises political strategies to provide solutions to challenges and conflicts, ensuring continuous improvement in the quality of education. This research aims to describe the political strategies employed by the headmaster of MIN 2 Kediri to enhance educational quality. This field research adopts a qualitative approach using in-depth interviews, observations, and documentation techniques. The findings reveal that: (1) The orchestra leadership model, which leans toward the four leadership styles of Gatto and Salusu, used by the head of MIN 2 Kediri, shapes and determines political strategies to achieve the school's goals in improving the quality of education; (2) many challenges and conflicts are resolved through solutions provided using the political strategies implemented by the headmaster, resulting in sustainable improvements in education quality. The conclusion of this study is that the skillfulness of the headmaster of MIN 2 Kediri in formulating political strategies and committing to wisely implementing planned actions facilitates the madrasa in achieving its goals. These goals include having a good reputation, gaining the trust of the community, and accommodating nearly 1,000 students with both academic and non-academic achievements in a warm and supportive madrasa environment.